Invisible - Gonzalez, Christina Diaz, 1969-; Epstein, Gabriela; Pien, Lark (New York, NY : Graphix, an imprint of Scholastic, 2022)
"Can five overlooked kids make one big difference? There's George: the brain; Sara: the loner; Dayara: the tough kid; Nico: the rich kid; and Miguel: the athlete. And they're stuck together when they're forced to complete their school's community service hours. Although they're sure they have nothing in common with one another, some people see them as all the same: just five Spanish-speaking kids. Then they meet someone who truly needs their help, and they must decide whether they are each willing to expose their own secrets to help--or if remaining invisible is the only way to survive middle school"--
Keywords: Children of minorities -- Comic books, strips, etc; Minority students -- Comic books, strips, etc; Friendship in adolescence -- Comic books, strips, etc; Identity (Psychology) -- Comic books, strips, etc; Middle schools -- Comic books, strips, etc; Children of minorities -- Fiction; Minority students -- Fiction; Friendship -- Fiction; Identity -- Fiction; Middle schools -- Fiction; Cartoons and comics; Graphic novels; School comics